Epidemiological Characterizations, New Localities, and a Checklist of the Known Scorpions in the Kurdistan Region, Northern Iraq - Fenik Sherzad Hussen; Hamid Saeid Kachel; Gzng Hama; Edi Kachal; Masoud Slo; Ihsan Hiwil; Ayoub Ibrahim Ahmed (Tehran University of Medical Sciences, 2023)
Background: Annually, thousands of scorpion stings and rare mortalities are recorded in the Kurdistan Region of Iraq. In the present study, we prepared a checklist for the geographical distribution of scorpion fauna composition, new localities data, and scorpion sting profile for the years 2019-2020 in the region. Methods: Random field surveys for scorpion collection were carried out in 22 localities in the Kurdistan Region from June 2020 to October 2021. Clinical data related to scorpion stings in 2019 and 2020 were obtained from the medical records of public health offices in the region. Results: In this survey, 166 specimens were collected. They were composed of seven scorpion species belonging to three families including: Buthidae, Hemiscorpiidae, and Scorpionidae. The collected species were Androctonus crassicauda, Compsobuthus matthiesseni, Hottentotta saulcyi, Mesobuthus mesopotamicus, Orthochirus fomichevi, Hemiscorpius lepturus, and Scorpio kruglovi. Moreover, three scorpion species comprising Buthacus tadmorensis, Hottentotta mesopotamicus, and Calchas anlasi were recorded in the previous study conducted in the Kurdistan region. In 2019-2020, 3726 scorpion stings were reported, with a peak in the summer season. Most of the patients were 15-49 years old. In the current study, medically significant scorpion species have been identified. Conclusion: The outcome of the present work will increase the awareness of the Kurdish community regarding the distribution of dangerous scorpion species and consequently reduce their stings.